2014
DOI: 10.2522/ptj.20130567
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapists' Clinical Knowledge of Multidisciplinary Low Back Pain Treatment Guidelines

Abstract: The survey identified varied understanding of CPGs when making decisions that were similar in recommendation to the CPGs. No single predictor for correct responses for LBP CPGs was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…Although the sample size in the present study is similar to that in previous studies [6,30], larger multi-center cohorts will be required to increase generalizability. Third, we did not investigate PT's knowledge about pain neuroscience [31], their attitude toward biopsychosocial perspectives for LBP management [24,32,33], and their adherence to clinical practice guidelines for LBP management [34]. These potential confounders should be considered in future studies with larger samples of PTs to help identify the contributing factors for increasing the ability of PTs to understand a patient's psychological status through physical therapy evaluation.…”
Section: Limitationsmentioning
confidence: 99%
“…Although the sample size in the present study is similar to that in previous studies [6,30], larger multi-center cohorts will be required to increase generalizability. Third, we did not investigate PT's knowledge about pain neuroscience [31], their attitude toward biopsychosocial perspectives for LBP management [24,32,33], and their adherence to clinical practice guidelines for LBP management [34]. These potential confounders should be considered in future studies with larger samples of PTs to help identify the contributing factors for increasing the ability of PTs to understand a patient's psychological status through physical therapy evaluation.…”
Section: Limitationsmentioning
confidence: 99%
“…Hendrick et al [5] found that less biomedical oriented approach was associated with adherence to LBP practice guidelines. Therefore, we contend that the management of LBP from both biomedical and behavioral perspectives and other potential factors may be associated with adherence to guidelines [5] [6], for example, demographic factors, the highest education level attained, the attitude of therapists towards self-directed learning to facilitate evidence-based clinical practice (e.g. participation in workshops and conferences, and engaging in literature review).…”
Section: Introductionmentioning
confidence: 99%
“…Such deficiencies in patient knowledge and practice may be attributed to related deficiencies in knowledge or educational role among their caregivers. In agreement with this explanation, Learman et al (2014) in a study in the United States and Canada found that only 16.6% of the participating physiotherapists correctly answered questions regarding LBP imaging, appropriate medication, and advice to stay active. The application of the present study instruction protocol had a positive impact on participants' knowledge and reported practice.…”
Section: Discussionmentioning
confidence: 84%